The Effect of Goodplant and Hantu Plant Growth Regulator (ZPT) Applicationon the Growth and Production of Pakcoy Crop (Brassica rapa L.) Using Hidroponic Axis System - Fauzi Irawan (Universitas 17 Agustus 1945 Samarinda, 2019)
The purpose of this research is to study the effect of Goodplant and ZPT Hantu concentration and their interaction on the growth and production of Pakcoy cropusing hydroponic axis system, and to obtain their proper concentrations for the best growth and production of Pakcoy crop.The study was conducted for three months from February to April 2017, from the time of seed preparation, land preparation until harvest time. The research site was conducted at Sumber Sari village, Barong Tongkok Subdistrict, Kutai Barat District. This study used a Completely Randomized Design (RAL), with 4 × 4 factorial experiment and 3 replications, consisting of 2 factors. Factor I is the concentration of Goodplant (N) consists of 4 levels, namely: no Goodplant application or control (n0), 5 ml 1-1 water (n1), 10 ml 1-1 water (n2), and 15 ml 1-1 water (n3). Factor II is the concentration of ZPT Hantu (H), consisting of 4 levels, ie: no ZPT Hantu application or control (h0), 1 ml 1-1 water (h1), 2 ml 1-1 water (h2), and 3 ml 1-1 water (h3).Goodplant treatment (N) affected very significantly on the plant height, leave number and weight of wetcrop. ZPT Hantu (H) treatment affected very significantly on the plant height, leave number and weight wetcrop.The interaction betweenGoodplant and ZPT Hantu(NxH) affected very significantlyon the plant height at 14 daysafter planting, plant height at 28 daysafter planting, number of leaves at 28 daysafter planting and weight of wetcrop; it affected significantly on the plant height at 21 daysafter planting; but it had no significant effect on the number of leaves at 14 days after planting and leave number at 21 days after planting.